Meningkatkan Keterampilan Pedagogik Guru melalui Metode Pembelajaran Inovatif Berbasis Teknologi Digital di Institut Attarkiyah Islamiah, Thailand Selatan - Akhyar, Yundri; Ningsih, Wirda; Guswanti, Nelia (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The low level of pedagogical skills among teachers in designing technology-based learning presents a significant challenge at Attarkiyah Islamiah Institute, Southern Thailand. Teachers face difficulties in creating digital teaching materials, utilizing interactive media, and fostering collaboration for instructional innovation. This community service project aimed to enhance teachers’ pedagogical competence through contextual, collaborative, and practical technology-based training. The method used was Participatory Action Research (PAR) with a participatory training approach, hands-on practice (microteaching), group work, and pre- and post-intervention evaluations. Twenty teachers from various disciplines participated in the program. The results indicated a significant improvement in three key areas: (1) the ability to design digital learning, (2) the skill to use interactive digital media, and (3) collaboration in developing innovative learning products. The training fostered a shift in teachers’ work culture—from individualistic to collaborative, and from passive to active and innovative. Moreover, the program reinforced the relevance of the TPACK framework, the learning-by-doing approach, and the Professional Learning Community (PLC) model in the context of Islamic education within a minority community. This initiative demonstrates that collaborative, practice-based training tailored to local values is effective in developing teacher competencies and promoting meaningful transformation in teaching practices.